Analysis of Cut Size Paper Cutting Machine Performance Using Total Productive Maintenance Concept (Case Study: PT. RST) - Mustafa, Rolandi; Susilawati, Anita; Mulyadi, Ismet Hari (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2024)
PT. RST, a leading paper factory in Indonesia, prioritizes timely production by optimizing productivity, efficiency, and paper quality. This study assesses the reliability of the Cut Size (CS) paper cutting machine, which is enhanced through the implementation of Total Productive Maintenance (TPM) as a management philosophy to ensure high-efficiency operations. To evaluate machine performance, Overall Equipment Effectiveness (OEE) measurement is used. From data collected from January to September 2023, an analysis is conducted to improve the performance of the CS machine, which has not met its set target. The average OEE value of 70.9% falls short of the target of 72%. This research aims to improve the performance of the CS machine through the TPM approach, focusing on the Focused Maintenance pillar. Using tools such as Pareto diagram, why-why analysis, fishbone diagram, and the 5W1H method, several sources of problems causing the decrease in OEE value will be identified and addressed.